A multiplex microplatform for the detection of multiple DNA methylation events using gold–DNA affinity. Issue 19 (1st September 2017) - Sina, Abu Ali Ibn; Foster, Matthew Thomas; Korbie, Darren; Carrascosa, Laura G.; Shiddiky, Muhammad J. A.; Gao, Jing; Dey, Shuvashis; Trau, Matt
Abstract : We report a new multiplexed strategy for the electrochemical detection of regional DNA methylation across multiple regions. Abstract : We report a new multiplexed strategy for the electrochemical detection of regional DNA methylation across multiple regions. Using the sequence dependent affinity of bisulfite treated DNA towards gold surfaces, the method integrates the high sensitivity of a micro-fabricated multiplex device comprising a microarray of gold electrodes, with the powerful multiplexing capability of multiplex-PCR. The synergy of this combination enables the monitoring of the methylation changes across several genomic regions simultaneously from as low as 500 pg μl −1 of DNA with no sequencing requirement.